1984
DOI: 10.1212/wnl.34.11.1516
|View full text |Cite
|
Sign up to set email alerts
|

Parkinsonism and basal ganglia infarcts

Abstract: A subacute parkinsonian syndrome was seen in three patients with CT evidence of basal ganglia infarcts. The clinical picture improved spontaneously, making the diagnosis of idiopathic Parkinson's disease untenable, and other causes of parkinsonism were not detected. This extrapyramidal syndrome was therefore compatible with "vascular parkinsonism," even though it lacked features often ascribed to this syndrome, such as a history of previous strokes and the presence of dementia and corticospinal tract signs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
50
0
4

Year Published

1997
1997
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(61 citation statements)
references
References 0 publications
7
50
0
4
Order By: Relevance
“…nvoluntary abnormal movements (IAMs) caused by strokes are relatively common, [1][2][3][4] and chorea, [3][4][5][6][7][8][9][10][11][12][13][14][15] tremor, [16][17][18][19][20][21][22][23][24][25][26][27][28][29] dystonia, [30][31][32][33][34][35][36][37][38][39][40][41][42][43] parkinsonism, [44][45][46][47][48][49][50]…”
mentioning
confidence: 99%
“…nvoluntary abnormal movements (IAMs) caused by strokes are relatively common, [1][2][3][4] and chorea, [3][4][5][6][7][8][9][10][11][12][13][14][15] tremor, [16][17][18][19][20][21][22][23][24][25][26][27][28][29] dystonia, [30][31][32][33][34][35][36][37][38][39][40][41][42][43] parkinsonism, [44][45][46][47][48][49][50]…”
mentioning
confidence: 99%
“…In addition, the presence of vascular encephalopathy, or even the existence of vascular risk factors, may aggravate the symptomatic picture in a patient with known PD (Papapetropoulos et al, 2004). The most relevant clinical characteristics of VP include: gait disorder, predominance in lower half of the body, postural instability, stiffness, pyramidal signs, and poor or no response to Ldopa (Tolosa et al, 1984;Trenkwalder et al, 1995), all of them occurring in a patient with evidence of cerebrovascular damage with no signs of other degenerative diseases, intake of antidopaminergic drugs, or hydrocephalus that could induce parkinsonism. Final diagnosis is made by post-mortem histological confirmation (absence of depigmentation or presence of Lewy bodies in substantia nigra) (Jellinger et al, 1996).…”
Section: Vascular Pseudoparkinsonism (Vp)mentioning
confidence: 99%
“…In 1929, Critchley [1]designated such cases as ‘arteriosclerotic parkinsonism’, reporting its clinical characteristics as compared to idiopathic Parkinson’s disease (IPD) consisting of rapid progression, symmetrical symptoms, absence of tremor and plastic rigidity instead of cogwheel rigidity. While he related the symptoms to vascular changes in the globus pallidus and, to a lesser extent, the substantia nigra, later autopsy- or neuroimaging-based studies have related parkinsonism to symmetrical vascular lesions in the putamen [2, 3, 4, 5, 6, 7]or cerebral white matter [8, 9, 10]. Experimental and human autopsy studies have demonstrated that dopaminergic nerve terminals [11], GABA/substance P neurons (which give rise to the indirect pathway [62]) [12], dopamine receptors [13]and nicotinic acetylcholine receptors [14]in the striatum are highly vulnerable to ischemia, which may result in an increased susceptibility to parkinsonism.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, systematic studies are required to specify vascular lesions that are pathogenetically related to parkinsonism and to determine symptomatic and neuroimaging criteria for differentiating VP from IPD. The symptomatic characteristics of IPD are, in general, presence of 4- to 6-Hz resting tremor and cogwheel rigidity that are usually asymmetric and a clear response to L -dopa [25, 26], whereas those of VP are history of stroke [3], absence of tremor [1], absence of ‘true’ rigidity [27]and lack of response to L -dopa [3]. Furthermore, neuroimaging studies have reported that the width of the substantia nigra pars compacta (SNpc) was decreased in patients with IPD [28, 29, 30, 31]but not in patients with suspected VP [30].…”
Section: Introductionmentioning
confidence: 99%